Impact of clavicular length change on clinical outcomes after surgical treatment of nonunion: A retrospective study - Dong Hwi Kim; Hyung Seok Park; Yong Jin Cho; Jong Hyeon Nam; Chae Hun Lee; GwangChul Lee (Journal of Orthopaedic Surgery)
Purpose Although clavicular fracture nonunion is uncommon, it can lead to pain and alterations in clavicular length, potentially affecting shoulder function. This study investigated the relationship between clavicular length changes and clinical outcomes following nonunion treatment. Methods This retrospective study included 30 patients who underwent surgical treatment for clavicular nonunion between January 2013 and December 2021. The clavicle length was measured pre- and postoperatively using anteroposterior radiography. Clinical evaluation involved measuring pre- and postoperative outcomes using the Constant-Murley scoring system. Subgroup analysis was performed by dividing patients into two groups based on the median clavicle length difference. Results The mean age was 45.8 years, and the mean follow-up period was 5.8 years. Osseous union was achieved in all cases. The mean clavicle length difference was 5.57 ± 8.45 mm, indicating a predominance of shortening in the affected clavicle. Functional outcomes demonstrated significant improvement following surgical intervention ( p < .001). A weak negative correlation (r = −0.19, p = .296) was observed between clavicle length difference and score improvement. Subgroup analysis revealed no statistically significant differences in clinical outcomes between the low and high length difference groups ( p = .757). Conclusion Surgical treatment of clavicular nonunion results in significant functional improvement. However, the extent of clavicular length change does not appear to be a major determinant of clinical outcomes. This finding has important implications for surgical planning and patient management in cases of clavicular nonunion.